PENGEMBANGAN MEDIA PEMBELAJARAN E-LKS BERBANTU EDMODO PADA MATERI BARISAN DAN DERET ARITMATIKA KELAS XI SMA MUHAMMADIYAH BRAJA SELEBAH T.P 2020/2021 - Yanu Wardeni Kristanto; Rina Agustina; Nurul Farida (Universitas Muhammadiyah Metro, 2022)
The purpose of this study was to produce e-LKS media assisted by Edmodo on valid and practical Arithmetic Rows and Series materials. This study uses the Research and Development (R & D) method. This research was conducted at SMA Muhammadiyah Braja Selebah. The research subjects were students of class XI SMA Muhammadiyah Braja Selebah. The object of this research is the e-LKS Barisan and Arithmetic Series assisted by Edmodo. Data collection techniques used interviews and validation questionnaires from material, language, media experts and practicality questionnaires from student responses. Based on the results of the study, it was concluded that the E-LKS Barisan and Arithmetic Series assisted by Edmodo was declared very valid and very practical, with an average percentage of validity test results of 87.33% and an average percentage of practicality test results of 83.25%.